Determination of zinc, nickel and cadmium in natural water samples by flame atomic absorption spectrometry after preconcentration with ion exchange and flotation techniques - Akcin, Nurgul; Koyuncu, Ikbal; Akcin, Goksel (WALTER DE GRUYTER GMBH, 2011)
Two preconcentration techniques, ion exchange and flotation, were used for the determination of zinc (Zn), nickel (Ni) and cadmium (Cd) in natural water samples. In the first part of our work, the adsorption of zinc(II), nickel(II) and cadmium(II) on Lewatit TP 207 chelating resin containing iminodiacetate groups was studied at different pH values by a batch process. The effects of parameters such as amount of resin, contact time, pH and initial metal concentration on the ion exchange separation were investigated. For the determination of the adsorption behavior of the resin, the adsorption isotherms of metal ions were also studied. The concentrations of metal ions were measured by batch techniques and with atomic absorption spectrometry analysis. Adsorption analysis results obtained at various concentrations showed that the adsorption pattern on the resin followed Langmuir and Freundlich isotherms. The efficiency of removal is higher for Ni and Zn than Cd ions. Here, we report the method that is applied for the sorption and separation of some toxic metals from the solutions. In the second part of our work, the flotation technique was used for preconcentration. The ability of Co(III) hexamethylenedithiocarbamate, Co(HMDTC) 3, as a flotation collector for metals from natural waters was investigated. The flotation method was compared with the ion exchange method. The recoveries of Zn, Cd and Ni from natural water samples were approximately 99%. Our results showed that the two methods were very effective, but the flotation results were higher than the ion exchange results. In the present study, a method was described for the determination of Zn, Ni and Cd by flame atomic absorption spectrometry (FAAS) after preconcentration and separation in water by ion exchange resin and flotation. Results of these two methods are compared. Analytical parameters such as precision and accuracy of methods were also studied. The equilibrium experimental results of Zn, Ni and Cd ions exchanged were fitted by Langmuir-Freundlich adsorption isotherm models.
Keywords: Cd(II); flotation; Freundlich isotherm; Langmuir isotherm; Lewatit TP 207; Ni(II); Zn(II); SOLID-PHASE EXTRACTION; SOLVENT-EXTRACTION; HEXAMETHYLENEDITHIOCARBAMATE; SEPARATION; REMOVAL; COPPER; IRON; LEAD; Chemistry